Strategic Instructional Organization for the Development of the Four Arabic Language Skills - Zulfan Syahansyah; Muhammad Amin Fathih; Muhammad Rauhul Mufid (Al-Wazan: Journal of Arabic Education, 2026)
Arabic language learning in Islamic boarding schools (pesantren) often faces challenges in integrating communicative approaches that emphasize speaking skills with traditional approaches focused on the mastery of Arabic grammar (nahwu-sharaf) and the reading of classical Islamic texts (kitab kuning). As a result, the development of the four language skills listening (istima'), speaking (kalam), reading (qira'ah), and writing (kitabah) is frequently unbalanced. This study aims to analyze the instructional organization strategies employed in teaching the four Arabic language skills at Darul Khoirot Islamic Boarding School in Malang. A qualitative approach with a case study design was adopted. Data were collected through participant observation, in-depth interviews with the kiai, teachers, and students, as well as document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that listening skills are developed through authentic audio exposure and speech activities (muhadharah), speaking skills through the implementation of a comprehensive Arabic-speaking environment (bi'ah arabiyah) and daily conversations (muhadatsah yaumiyah), reading skills through the integration of thematic reading (muthala'ah) and grammatical analysis of classical texts, and writing skills through sequential stages of imla', insya' muwajjah, insya' hurr, khat, and peer correction. The study demonstrates that Darul Khoirot successfully integrates communicative language teaching with traditional grammar-based instruction within a unified learning ecosystem. This model offers an alternative framework for developing holistic and contextual Arabic language education in pesantren.